PEMANFAATAN WEBSITE UNTUK PROMOSI DAN PEMASARAN BATIK TRADISIONAL WARNA ALAM GUNA KELESTARIAN BUDAYA BATIK JAMBI: Batik, Technology, Website, Marketing - -, Nilawati (JURNAL AKADEMIKA, 2018)
Jambi has batik that is different from other batik in Indonesia, Jambi batik craftsmen are spread in several districts, in Tanjung Jabung Timur, Tanjung Jabung Barat, Kerinci, Merangin, Sarolangun, Muara Jambi, Muara Bungo, Muara Tebo, Batang Hari, and Jambi City. This research was conducted in one of the centers of batik craftsmen specializing in raw materials for natural dyes in Jambi Province. This research aims to help artisans develop their business. During this time the business activities of Bahri Batik craftsmen are carried out conventionally, both in production and marketing. This causes a long production time, very small business transactions. Need to develop the conventional process to the process of using technology. The methodology used in developing this process, using the waterfall model methodology, begins with 1). Phase Analysis, 2). Design Phase, 3). Implementation Phase, 4). Phase Testing, and 5). Desimination Phase. At this phase the two forms of technology are used 1). Production technology, application of lathes to produce dyes, computer applications for batik design, electric canting, 2). Marketing Technology, designed a website as a medium of marketing and online transactions for artisans. This research produced a website as an online marketing and online transaction media for Bahri Batik, increasing skills for craftsmen in the use of technology, both production technology and marketing technology.